Modes and geometry of crustal-scale detachment folding in hot orogens—Insights from physical modeling - Krýza, Ondřej; Závada, Prokop; Shu, Tan; Semerád, Jiří (Frontiers in Earth Science, 2022)
Detachment folding can be defined as the displacement and buckling of a competent layer above a rheologically weak horizon during tectonic shortening, frequently addressed in the context of salt tectonics. More recent studies have focused on influence of detachments in large-scale lithospheric deformation where the detachment horizon is represented by partially molten lower crust. This study addresses the geometric, kinematic and dynamic behaviour of crustal-scale detachment folds using heated paraffin wax as an analogue for partially molten lower crust. Various thermal and shortening rate scenarios were tested in order to characterize deformation patterns within hot orogens in general, and to find an appropriate range of temperature gradients and shortening rates for the detachment folding regime. Five different regimes of lower crustal deformation were identified: 1. homogeneous thickening or bulging, 2. short-wavelength folding, 3. development of diapir-shape folds or ductile faults, 4. detachment folding and 5. formation of lower crustal finger-like protrusions. Models are compared to various natural prototypes worldwide, in particular a series of metamorphic domes in the Central Asian Orogenic Belt (CAOB). Detailed analysis of the kinematic-dynamic evolution of the detachment folding scenario revealed an asymmetrical evolution of the folds associated with rotation of the limbs, as well as flexural flow of the lower weak mushy crust around the molten core. Pressure gradients in the fold cores saturated by melt controlled the sequential injections and outflows of partially/molten material between folds’ cores and the melt source layer at the base of the system. This resulted in accumulation of melt in the foreland of the accretionary zone, with higher melt absorption potential for newly developed folds. These observations may have significant implications for the development of pseudo-symmetrical metamorphic domes in the CAOB.